Drugs associated with gingival enlargement: a review of the scientific literature on clinical characteristics and related factors - Vargas Cornejo, Hector Martin (2026)
Drug-induced gingival enlargement is a multifactorial condition that compromises the periodontal health of patients undergoing prolonged treatments. This review of the scientific literature aimed to identify the medications most frequently associated with this condition, describe their clinical characteristics, and analyze related factors. The study was conducted following the PRISMA 2020 statement. A search for articles was carried out between November 11, 2024, and February 5, 2025, in the PubMed, Scopus, ProQuest, and EBSCOhost databases. Clinical and observational studies in humans (cross-sectional and longitudinal) on gingival enlargement associated with anticonvulsants, calcium channel blockers, and immunosuppressants were included. Of the 2,152 records identified, 2,094 were excluded after title and abstract screening, and 34 after full-text review because they were case reports, case-control studies, animal or cellular studies, or reviews. As a result, 11 studies were included. The collected evidence showed that phenytoin presented prevalences close to 50%; amlodipine, between 1.7% and 37%; and cyclosporine A, between 25% and 53%. The most influential factors were dosage, duration of treatment, and level of oral hygiene, whereas age and sex showed a less consistent relationship. It is concluded that the available evidence significantly associates certain drugs with gingival enlargement, highlighting the importance of periodontal monitoring and prevention in medicated patients.